In Vitro Antiglycation Potential of Erva-Baleeira (Varronia curassavica Jacq.) - Winner Duque Rodrigues; Felipe Nunes Cardoso; Amanda Martins Baviera; André Gonzaga dos Santos (MDPI AG, 2023)
Background: Varronia curassavica Jacq. (Boraginaceae) is traditionally used in the treatment of inflammatory processes. The ethanolic extract of its leaves (EEVc) showed anti-inflammatory properties and low toxicity. Medicinal plants have aroused interest for their antiglycation activities. The formation and accumulation of advanced glycation end products (AGEs) are associated with several chronic diseases. The objective of this study was to evaluate the antiglycation potential of EEVc and two isolated compounds. Methods: The compounds brickellin and cordialin A were obtained by chromatographic methods and identified by spectrometric techniques. Analysis of fluorescent AGEs, biomarkers of amino acid residue oxidation, protein carbonyl groups and crosslink formation were performed in samples obtained from an in vitro model system of protein glycation with methylglyoxal. Results: EEVc, brickellin and cordialin A significantly reduced the in vitro formation of AGEs, and reduced the damage caused by oxidative damage to the protein. Conclusions: According to the results, EEVc, brickellin and cordialin A are potential candidates against AGEs formation, which opens the way to expand the therapeutic arsenal for many pathologies resulting from glycoxidative stress.